2022
DOI: 10.1155/2022/9995335
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Detoxification of Congo Red and Brilliant Green Dyes Using Chemically Processed Brassica Oleracea Biowaste from Waste Water

Abstract: Water pollution being a potential risk to mankind is treated in several ways which includes chemical treatments. Among them, adsorption took a prominent position for the removal of many hazardous dyes from waste water. Here in this study, an environment-friendly, inexpensive, and broadly available leaves of Brassica oleracea were utilized for adsorption of two carcinogenic dyes, i.e., Congo red and brilliant green. The adsorbent Brassica oleracea leaves were collected, dried, and characterized by FTIR and SEM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The high sorption capacities at less contact time are due to the large number of vacant sites available on the surface of the adsorbent. The graph becomes linear as the time increases due to the non-availability of vacant spaces and the repulsive forces operates for the upcoming ions by the already entrapped Cr(III)/fluorescein ions [18]. also been observed that when contact times were further increased for Cr(III) and fluorescence, the adsorption capacities decreased and finally became constant.…”
Section: Effect Of Contact Timementioning
confidence: 90%
See 3 more Smart Citations
“…The high sorption capacities at less contact time are due to the large number of vacant sites available on the surface of the adsorbent. The graph becomes linear as the time increases due to the non-availability of vacant spaces and the repulsive forces operates for the upcoming ions by the already entrapped Cr(III)/fluorescein ions [18]. also been observed that when contact times were further increased for Cr(III) and fluorescence, the adsorption capacities decreased and finally became constant.…”
Section: Effect Of Contact Timementioning
confidence: 90%
“…The influence of temperature changes on the batch ion exchange sorption of Cr(III) and fluorescein with anionic MFZPI and cationic SMFZPI adsorbents were studied in the temperature range of 293-333 K. All the experiments were done in replicates at an agitation speed of 250 rpm, the solutions were filtered, and the filtrates were investigated by atomic absorption spectroscopy (AAS) for Cr(III) sorption and visible spectrophotometer for fluorescein removal. The maximum sorption (q e , mg/g) and removal percentage (R%) of Cr(III) and fluorescein by MFZPI and SMFZPI were estimated with the following equations [18] (Equations ( 1) and ( 2)).…”
Section: Batch Ion Exchange Adsorption Of Cr(iii) and Fluoresceinmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of pHpzc is to determine the influence of pH range on the active site of the surface adsorbent. The value of pH > pHpzc induces optimum adsorption of cationic dyes due to negative charge increases on adsorbent (Kanwal et al, 2022) . RhB has a positive charge in the solvent, then tends to adsorb at a higher pH value than the pHpzc condition (Ribeiro dos Santos et al, 2019) .…”
Section: Optimization Of Operational Conditionsmentioning
confidence: 99%